VIP1, a bZIP protein, interacts with the catalytic subunit of protein phosphatase 2A in Arabidopsis thaliana - Yoon, Hyuk Sung (Plant Signal Behav, 2019)
VirE2-INTERACTING PROTEIN1 (VIP1) is a basic leucine zipper protein in Arabidopsis thaliana. VIP1 changes its subcellular localization from the cytoplasm to the nucleus when cells are exposed to mechanical or hypo-osmotic stress. The nuclear localization of VIP1 is inhibited either by inhibitors of calcium signaling or by inhibitors of protein phosphatases 1, 2A and 4 (PP1, PP2A and PP4, respectively). VIP1 binds to the PP2A B”-family subunits, which have calcium-binding EF-hand motifs and which act as the regulatory, substrate-recruiting B subunit of PP2A. The VIP1 de-phosphorylation can therefore be mediated by PP2A. However, details of the PP2A-mediated de-phosphorylation of VIP1 are unclear. Here, with yeast two-hybrid assays and in-vitro pull-down assays, we show that VIP1 does not interact with the scaffolding A subunit of PP2A, but that VIP1 does interact with the catalytic C subunits. Our data raise the possibility that not only the B”-family B subunit of PP2A but also its C subunit contributes to the PP2A-mediated de-phosphorylation of VIP1.